(Post)pandemic challenges in pedagogical and psychological work with children and youth - Róg, Anna (Wydawnictwo Uniwersytetu Jana Kochanowskiego w Kielcach, 2023)
The COVID-19 pandemic, due to its specificity – especially very strict sanitary regimes – has brought many negative effects in the area of the psychosocial functioning of society, including children and youth, which has translated into a significant deterioration of the mental condition of this social group.